Peran Mentor Bisnis Bagi TKI Pasca Migrasi Untuk Berwirausaha - Sayid Abas; Rochmat Aldy Purnomo (Fakultas Ekonomi Universitas Islam 45, 2017)
Indonesia has a large population and potential of natural resources which is resulting in problems of human resources, natural resources, and environment. The high number of productive age also brings the problems of employment and unemployment. Moreover, education has not been able to guarantee the employment opportunities. The situation becomes ironic when people go abroad to looking for jobs without a sufficient skill. The researcher tries to give contribution towards the problem by explaining the importance of entrepreneurship. This descriptive research uses a qualitative approach. The sample is the Migrant Workers (TKI) in Ponorogo Regency who get support from family to work abroad again. The migrant workers work abroad because of the economic needs. The migrant workers who have returned home, prefer to start being an entrepreneur than to work abroad again